RAJA AMPAT LOCAL GOVERNMENT LEADERSHIP MODEL IN THE DEVELOPMENT OF ISLAMIC EDUCATION IN PAPUA: A Phenomenological Study In Raja Ampat District - Umlati, Abdul Faris; Nur, Indria (Pascasarjana IAIN Sorong, 2023)
This article aims to analyze the local government leadership strategies implemented in Raja Ampat district in developing Islamic education; this type of research uses Phenomenological research with a descriptive qualitative approach. The data collection methods used are observation, interview and documentation methods and fgd. The results showed that 1). The local government leadership model in the development of Islamic education in Papua by establishing transformative leadership by creating local government policies through local regulations, Establishing a Policy on the Construction of Houses of Worship (Mosques) through the Regional Budget (APBD); Policy on Providing Incentives to Mosque Takmir, Imams, through the APBD; Empowering religious social organizations; Providing study fee assistance to mosque takmir educators, imams and religious leaders that not all local governments carry out this strategy6; 2). The Raja Ampat local government develops its role as a regulator, facilitator, social welfare provider and monitoring and evaluator, resulting in better quality and quantity of mosque/mushallah worship facilities and non-formal education institutions; increasing the quality of education services and strengthening smart, qualified and competitive human resources.